2021
DOI: 10.1007/s40615-021-00973-1
|View full text |Cite
|
Sign up to set email alerts
|

Global Food Insecurity and African, Caribbean, and Black (ACB) Populations During the COVID-19 Pandemic: a Rapid Review

Abstract: Background The global food insecurity reinforces the ongoing impact of COVID-19 on human health and mortality. Although literature remained sparse, reports indicated that food insecurity is disproportionately high among African, Caribbean, and Black (ACB) population since the outset of COVID-19. Hence, we assessed the food insecurity conditions of ACB populations globally during the COVID-19 pandemic. Methods Comprehensive searches in CINAHL, Medline (Ovid), PubMed (Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…These measures (though arguably theoretically sound), have also been impractical for various segments of populations across the world, fundamentally due to access inequities in various settings from a lack of adequate housing conditions and facilities or residence in overcrowded slums/housing shelters, poor access to power supply and electricity, to a lack of clean water or hand sanitizers and poor access to safe and improved WASH facilities (17)(18)(19)(20)(21)(22). The health and economic consequences of COVID-19 have also exacerbated food insecurity and inequities in access to education and finance globally, especially in resource-constrained settings (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…These measures (though arguably theoretically sound), have also been impractical for various segments of populations across the world, fundamentally due to access inequities in various settings from a lack of adequate housing conditions and facilities or residence in overcrowded slums/housing shelters, poor access to power supply and electricity, to a lack of clean water or hand sanitizers and poor access to safe and improved WASH facilities (17)(18)(19)(20)(21)(22). The health and economic consequences of COVID-19 have also exacerbated food insecurity and inequities in access to education and finance globally, especially in resource-constrained settings (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…A major contribution of this work is to present a new multi-dimensional measure of food insecurity that strengthens the link between the level of food security as both an ethical and social responsibility issue. We suggest that the adoption and utilization of data produced by the FAI offers a number of policy and management implications to help bring about sustainable social change in the food supply chain and address this as a wicked social problem [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mental health disparities, in turn, can be attributed to socioeconomic challenges and difficulties in accessing care, which may ultimately result in more perpetual, lasting mental health impacts ( Saltzman et al 2021 ). Globally, COVID-19 has exacerbated health disparities among the African, Caribbean, and Black (ACB) populations owing to their lack of representation in decision-making and factors pertaining to cultural competency and appropriateness in health care ( Dabone et al 2022 ). In their retrospective ecological study, Chaudhuri et al (2021) found that minority ethnic groups (including Black ethnic minorities) experienced a greater risk of developing COVID-19 and poorer outcomes than their White counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%